2004
DOI: 10.1007/s00122-004-1827-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four flow cytometric SNP detection assays and their use in plant improvement

Abstract: Single nucleotide polymorphisms (SNPs) are attractive DNA markers due to their abundance and potential for use in automated high-throughput genotyping. Numerous SNP genotyping assays have been developed, but it is unclear which assays are best suited and most efficient for various types of plant improvement research. The objective of this study was to compare the accuracy, efficiency, and cost of four SNP genotyping assays: single-base extension (SBE), allele-specific primer extension (ASPE), oligonucleotide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…A total of 300 markers including 149 markers from transcribed (exon) sequences (Yang et al, 2004(Yang et al, , 2005a and 151 markers from intron sequences (Van Deynze et al, 2007) were used to genotype the collection of cultivated tomato varieties. We used multiple genotyping platforms including agarose gel electrophoresis for SNP detection as cleaved amplified polymorphic sequences (CAPS) and the LUMINEX 200 (Luminex, Corp., Austin, TX, USA) for detection of SNPs using allele-specific primer extension (ASPE) (Lee et al, 2004). The LICOR IR2 system (LICOR, Lincoln, NE, USA) was used for fragment analysis of SSR and InDel markers.…”
Section: Genotypingmentioning
confidence: 99%
“…A total of 300 markers including 149 markers from transcribed (exon) sequences (Yang et al, 2004(Yang et al, , 2005a and 151 markers from intron sequences (Van Deynze et al, 2007) were used to genotype the collection of cultivated tomato varieties. We used multiple genotyping platforms including agarose gel electrophoresis for SNP detection as cleaved amplified polymorphic sequences (CAPS) and the LUMINEX 200 (Luminex, Corp., Austin, TX, USA) for detection of SNPs using allele-specific primer extension (ASPE) (Lee et al, 2004). The LICOR IR2 system (LICOR, Lincoln, NE, USA) was used for fragment analysis of SSR and InDel markers.…”
Section: Genotypingmentioning
confidence: 99%
“…There are many considerations in selecting a SNP genotyping assay, and the choice usually depends on cost per data point and simplicity of data acquisition (Lee et al 2004). To obtain reliable and reproducible SNP genotyping results, we found that the MCA required relatively high quality and quantiWed DNA extracted using the CTAB extraction method, while the TaqMan assays produced high-quality genotypic data even with quick-extracted DNA (Bell-Johnson et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) markers are becoming widely used in soybean breeding and research (Hyten et al 2009b) because of their high frequency, widespread distribution throughout the genome (Choi et al 2007), and their suitability for high-throughput automated genotyping (Hyten et al 2008;Lee et al 2004;Schork et al 2000). Zhu et al (2003) found 3.68 SNPs per kilobase pair (kb) in 25 diverse soybean genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of SNP assays varies with SNP assay methods. Lee et al (2004) estimated the cost of reagents per simplex (per data point) reaction among four SNP genotyping assays to be $0.069-0.104. As SNPs continue to gain prominence in plant and animal genetic analysis, the cost effectiveness of SNP detection assays is likely to improve.…”
Section: Discussionmentioning
confidence: 99%